(untitled) (Heritage, 2025)
Using the example of three travelogues by Rade Drainac, "The Road to Ohrid", "On Lake Ohrid" and "Ohrid Meditations", we interpret the poetic dilemmas, decisions and characteristics of his work in the early 1930s. While in a broader sense the work is intended to stimulate scholarly interest in the literary topos of the city of Ohrid, in a narrower sense it interprets Drain’s version of neorealist literature and the so-called literary left front.